A charge integrator sensing circuit for real-time external compensation regardless of threshold voltages of organic light emitting diodes - Myung Gi Lim; Seung-Woo Lee (Journal of Information Display)
This paper proposed a novel sensing circuit using a charge integrator (CI) to compensate for the thin-film transistors (TFTs) in organic light-emitting diode (OLED) displays. A higher CI initialization voltage is commonly preferred for sensing various TFT characteristics, but this may turn on OLED with a low threshold voltage. The proposed sensing circuit separates the initialization voltages for the TFT and the CI, allowing accurate TFT current sensing regardless of OLED characteristics. The suggested method calculates the threshold voltage (VTH) and the transconductance parameter (K) of TFT using currents sensed at two gate–source voltages (VGSs) for compensation. Real-time compensation is achieved by performing sensing within vertical blanking time. We simulated compensation performance under ΔVTH and ΔK variations of ±0.5 V and ±10%, which demonstrated the current deviation decreased from a maximum of 70.20% to 1.07%. We then fabricated an 11-inch active-matrix OLED (AMOLED) panel to verify the compensation performance. The measurement results revealed that the current deviation decreased from a maximum of 38.11% to 2.55%. The compensation performance was successfully demonstrated with an 11-inch AMOLED panel. The proposed sensing circuit allows CI to be used regardless of OLED characteristics, making it suitable for a wider range of display applications.